The Financial Impact of ISO 14001 Certification: Top-Line, Bottom-Line, or Both? - De Jong, Pieter J.; Paulraj, Antony; Blome, Constantin (2014)
It is not easy being green, but it does beg the question: Does being green pay off on the bottom-line? Unfortunately, that question of becoming ISO 14001 to reap financial benefit remains widely unanswered. In particular, corporate practice is interested in how environmental management impacts firms’ finance through top-line impact, bottom-line impact, or both—as this paves the way for an investment of environmental management. As current findings are mixed, our study tracks financial performance of publicly traded US firms between 1996 and 2005 to test whether ISO 14001 leads to improved financial performance. Employing a rigorous event-study approach, we compare certified firms to different control groups based on several matching criteria that include industry, size, and/or ROA. In the short run, ISO 14001 certification makes only a minor impact on the bottom-line, according to our results. However, these same results show a significant financial improvement over the long haul with ISO 14001 certification. Additionally, this long-term improvement also makes a significant improvement in top-line performance. Thus, we conclude that environmental management pays off along both dimensions.
Keywords: Bottom-line impact; Top-line impact; Financial Performance; Event Study; Environmental management systems; ISO 14001